Molecular Phylogeny and Historical Biogeography of Goodyera R. Br. (Orchidaceae): A Case of the Vicariance Between East Asia and North America - Kim, Tae-Hee; Kim, Joo-Hwan (Frontiers in Plant Science, 2022)
Understanding of intercontinental distribution in Northern Hemisphere has attracted a lot of attention from botanists. However, although Orchidaceae is the largest group of angiosperms, biogeographical studies on the disjunctive pattern have not been sufficient for this family. Goodyera R. Br. (Tribe Cranichideae, Subfamily Orchidoideae, Family Orchidaceae) is widely distributed in temperate and tropical regions. Although phylogenetic relationship of Goodyera inferred from both morphological and molecular data has been conducted, the sampled taxa were mainly distributed in Asia regions that resulted non-monophyly of this genus. In this study, complete plastid genomes of Goodyera, generated by Next generation sequencing (NGS) technique and sampled in East Asia and North America, were used to reconstruct phylogeny and explore the historical biogeography. A total of 18 Goodyera species including seven newly sequences species were analyzed. Based on 79 protein-coding genes, the phylogenetic analysis revealed that Goodyera could be subdivided into four subclades with high support values. The polyphyletic relationships among Goodyera taxa were confirmed and the unclear position of G. foliosa was also resolved. The datasets composed of the fourteen CDS (matK, atpF, ndhK, accD, cemA, clpP, rpoA, rpl22, ndhF, ccsA, ndhD, ndhI, ndhA, and ycf1) showed the same topology derived from 79 protein-coding genes. Molecular dating analyses reveal the origin of Goodyera in the middle Miocene (15.75 Mya). Nearctic clade of Goodyera was diverged at 10.88 Mya from their most recent common ancestor (MRCA). The biogeographic reconstruction suggests that subtropical or tropical Asia is the origin for Goodyera and it has subsequent spread to temperate Asia during the Miocene. In addition, Nearctic clade is derived from East Asian species through Bering Land Bridge (BLB) during the Miocene. The speciation of Goodyera is most likely to have occurred during Miocene and climatic and geological changes are thought to have had a part in this diversification. Our findings propose both origin and vicariance events of Goodyera for the first time and add an example for the biogeographic history of the Northern Hemisphere.